1995
DOI: 10.1210/mend.9.1.7760845
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity and functional characterization of voltage-dependent calcium channels (CACN4) expressed in pancreatic beta-cells.

Abstract: Dihydropyridine-sensitive voltage-dependent calcium channels (VDCC) play a crucial role in insulin secretion. We recently have cloned a human alpha 1-subunit of the VDCC expressed in pancreatic beta-cells, designated CACN4. In this study we have isolated complementary DNAs encoding two forms of rat CACN4 (rCACN4A and rCACN4B) from a rat insulinoma RINm5F complementary DNA library. Rat CACN4A is a protein of 2203 amino acids and is the rat homolog of human CACN4, whereas rCACN4B lacks 535 amino acids in the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…Most probably, of the various L-type calcium channels present, the ĂĄ1D isoforms were affected by galanin, since Ăč_CTX GVIA decreased the portion of currents inhibited by the hormone. In accordance with our results, ĂĄ1C and ĂĄ1D subunits have previously been detected in endocrine pancreas (Seino et al 1992;Pollo, Lovallo, Biancardi, Sher, Socci & Carbone, 1993;Ihara et al 1995) and have also been found in a hamster insulinoma (HIT) cell line (Boyd et al 1991;Yaney et al 1992). In RINm5F cells, galanin-induced inhibition of ICa was similar to that induced by many other hormones.…”
Section: Discussionsupporting
confidence: 92%
“…Most probably, of the various L-type calcium channels present, the ĂĄ1D isoforms were affected by galanin, since Ăč_CTX GVIA decreased the portion of currents inhibited by the hormone. In accordance with our results, ĂĄ1C and ĂĄ1D subunits have previously been detected in endocrine pancreas (Seino et al 1992;Pollo, Lovallo, Biancardi, Sher, Socci & Carbone, 1993;Ihara et al 1995) and have also been found in a hamster insulinoma (HIT) cell line (Boyd et al 1991;Yaney et al 1992). In RINm5F cells, galanin-induced inhibition of ICa was similar to that induced by many other hormones.…”
Section: Discussionsupporting
confidence: 92%
“…VAMP-2, Rab3A, SNAP25A and synaptotagmin I are implicated in insulin exocytosis [44][45][46]. Voltage-dependent Ca 2+ channel Ca v 1.3 (α 1D ) subunit is involved in mediating beta cell insulin secretion in response to rising concentrations of glucose [47]. All these proteins are required for normal glucose-stimulated insulin secretion.…”
Section: Resultsmentioning
confidence: 99%
“…There is ample evidence that L-type VDCC play a pivotal role in beta-cell secretion, although the precise subunit composition of the channels involved and their metabolic modulation are not known [17,128]. This goal has been complicated by the fact that all types of VDCC, including the two L-type classes α1c and α1d and four different ÎČ subunits are expressed in pancreatic beta cells [46,47,129]. The regulated release of insulin from the beta cell seems to utilize a mechanism that is highly conserved across many cell types including neuroendocrine cells [130].…”
Section: Calcium Influx and Stimulation Of Exocytosismentioning
confidence: 99%